Relationship Between Anthropometric Characteristics And Spatio-temporal Parameters In Freestyle Swimming - Yagoubi , Adma (sports creativity, 2025)
The purpose of this study is to investigate the relationships between spatio-temporal parameters and it’s interdependence with some anthropometric measurements. 24 swimmers of national level were evaluated in competitive situation, on the 50 m and 100 m freestyle events, using the video recording method. The results show that the swimming speed increases principally as a function of the stroking length (r = 0.82), wich affects in its turn the swimming index for the two distances (r=0.92-0.93), The results highlighted the importance of anthropometric characteristics in particular, height and arm length, in a realization of sprint performance by positively influencing stroke length (r = 0.68-0.78), conversely these characteristics do not explain the increase in stroke rate. Stroke length and swimming index remain to be the best indicators of the propulsive efficiency and level of preparation; therefore it can be used for, control and design training program.